Penentuan Jalur Optimal Menggunakan Model Analisis Jaringan Untuk Pelayanan Pemadam Kebakaran - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1999)
The responding officer of fire emergency service needs fast movement capability to achieve the fire location. This institution has to be supported with information of traffic network, traffic density, hydrant location, and address all offire location. Geographical information system technology could be used to integrate all of these data in which easily accessed for optimal path network analysis modelling based on distance or travel time. This research deals with the network modelling for optimal path or fire emergency service by road network data of Yogyakarta. The road network only covers the main road of the Municipality of Yogyakarta. The results showed that the nearest distance path was not equivalent with the shortest time travel. It is recommended that in the day, travel time should be used, while in the night the shortest distance be used for analyzing optimal path.